Kajian Semantik dan Stilistika atas Makna Konotatif dalam Cerpen "Cara Ia Membangunkan Aku" Karya Musmarwan Abdullah: A Semantic and Stylistic Analysis of Connotative Meaning in the Short Story “Cara Ia Membangunkan Aku” by Musmarwan Abdullah - Gunawan, Dedek; Nalurita, Baiq Annisa Yulfana; Amelia, Fitri (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2026)
Connotative meaning refers to additional meaning that arises through social, cultural and psychological associations beyond the conceptual meaning of a word or expression. n Acehnese and broader Malay society, indirect language remains prevalent, including in literary works such as Cara Ia Membangunkan Aku by Musmarwan Abdullah. This study aims to describe and analyse the forms of connotative meaning found in the short story Cara Ia Membangunkan Aku. The study employs a qualitative descriptive approach with a semantic analysis. The research data consists of words, phrases, and sentences containing connotative meaning in the short story. Data collection techniques were carried out through intensive reading, note-taking, and analysis based on Geoffrey Leech’s theory of connotative meaning. The results of the study indicate the presence of 19 instances of connotative meaning, comprising 7 metaphors, 1 metonymy, 6 sarcasms, and 5 forms of politeness. Metaphors are the most dominant form and are frequently used to describe the psychological state of characters, life experiences, and social relationships. In addition to serving as an aesthetic element, the use of connotative meaning also reflects cultural values, politeness, and the implicit nature of Acehnese communication. Connotative meaning in the short story Cara Ia Membangunkan Aku plays a significant role in enriching meaning, building linguistic aesthetics, and representing the cultural identity of the Acehnese people. The dominance of metaphors demonstrates the strong use of figurative language as a means of conveying messages and reflecting the social life of the Malay community.